Simplified Model of PKCγ Signaling Dysregulation and Cytosol-to-Membrane Translocation Kinetics During Neurodegenerative Spinocerebellar Ataxia Type 14 (SCA14) - Aslam, Naveed; Alvi, Farah (Frontiers in Neuroscience, 2020)
Spinocerebellar ataxia type 14 (SCA14) is an autosomal neurodegenerative disease clinically characterized by progressive ataxia in the patient’s gait, accompanied by slurred speech and abnormal eye movements. These symptoms are linked to the loss of Purkinje cells (PCs), which leads to cerebellar neurodegeneration. PC observations link the mutations in PRKCG gene encoding protein kinase C γ (PKCγ) to SCA14. Observations also show that the link between PKCγ and SCA14 relies on a gain-of-function mechanism, and, in fact, both positive and negative regulation of PKCγ expression and activity may result in changes in cellular number, size, and complexity of the dendritic arbors in PCs. Here, through a systems biology approach, we investigate a key question relating to this system: why is PKCγ membrane residence time reduced in SCA14 mutant PCs compared to wild-type (WT) PCs? In this study, we investigate this question through two contrasting PKCγ signaling models in PCs. The first model proposed in this study describes the mechanism through which PKCγ signaling activity may be regulated in WT PCs. In contrast, the second model explores how mutations in PKCγ signaling affect the state of SCA14 in PCs. Numerical simulations of both models show that, in response to extracellular stimuli-induced depolarization of the membrane compartment, PKCγ and diacylglycerol kinase γ (DGKγ) translocate to the membrane. Results from our computational approach indicate that, for the same set of parameters, PKCγ membrane residence time is shorter in the SCA14 mutant model compared to the WT model. These results show how PKCγ membrane residence time is regulated by diacylglycerol (DAG), causing translocated PKCγ to return to the cytosol as DAG levels drop. This study shows that, when the strength of the extracellular signal is held constant, the membrane lifetime of mutant PKCγ is reduced. This reduction is due to the presence of constitutively active mutant PKCγ in the cytosol. Cytosolic PKCγ, in turn, leads to phosphorylation and activation of DGKγ while it is still residing in the cytosol. This effect occurs even during the resting conditions. Thus, the SCA14 mutant model explains that, when both DAG effector molecules are active in the cytosol, their interactions in the membrane compartment are reduced, critically influencing PKCγ membrane residence time.